Pemanfaatan Cangkang Kemiri Sebagai Katalis CaO (Candlenut Shell) yang Terimpregnasi KOH dalam Produksi Biodiesel Minyak Jelantah melalui Reaksi Transesterifikasi - Nur Sha’in; Anerasari Meidinariasty; Akbar Ismi Aziz Pramito (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The growing demand for environmentally friendly and renewable alternative fuels, with biodiesel being a prominent candidate. Waste cooking oil (WCO), a widely available household waste, is a promising feedstock but requires an efficient catalyst to improve the transesterification process. The objective of this research was to investigate the effect of CaO catalyst derived from candlenut shells impregnated with KOH, and to determine the optimum methanol-to-oil molar ratio and catalyst concentration. The results showed that the optimum condition was achieved at a 1:6 molar ratio with 1.5% catalyst, producing biodiesel with a density of 0.877 g/mL, viscosity of 4.6 cSt, acid value of 0.25 mg KOH/g, cetane number of 54.7, and yield of 85%, all in accordance with the Indonesian National Standard (SNI 7182:2015). GC-MS analysis revealed a total fatty acid methyl ester (FAME) content of 99.57%, dominated by compounds such as methyl oleate, methyl stearate, and methyl linoleate, indicating near-complete conversion. These findings confirm the potential of CaO-KOH catalyst from candlenut shell waste as an effective heterogeneous catalyst for producing high-quality and sustainable biodiesel.